Pendekatan Savi Model Examples Non Examples Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa smpn 1 Banjar Margo Kabupaten Tulang Bawang - Masnah Masnah (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
Learning PAI in class VIII of SMP Negeri 1 Banjar Margo is still lacking. In this shortage it is not because the teacher does not master the material, but does not know how to deliver the material properly and correctly, and the teacher does not use the teaching aids or media well in the student environment. Therefore the authors conducted Classroom Action Research (CAR) with the results of discussing the activeness of students in the first cycle who got a score of 5%, score b = 30%, score c = 65%. Learning outcomes M KKM, which gets a score of = 0%, score b = 27%, score c = 17%. Portfolio data that gets a score of = 3%, score b = 40%, score c = 57%. Cycle 2 Meeting 5, active learning that gets a score = 23%, score b = 45%, score c = 32%. Learning outcomes M KKM, which gets a score of = 23%, score b = 47%, score c = 23%. Portfolio data that gets a score of = 30%, score b = 47%, score c = 23%. Meeting 6, active learning that gets a score of = 30%, score b = 53%, score c = 17%. Learning outcomes ≥ KKM, which gets a score = 50%, score b = 40%, score c = 10%. Portfolio data that gets a score of = 40%, score b = 47%, score c = 13%. These three aspects have increased.